Kompabilitas Penggunaan Metode Omnibus Dalam Pembentukan Undang-Undang - Ibnu Sina Chandranegara (Jurnal Hukum IUS QUIA IUSTUM, 2020)
Each legal system has its own theory of statutory formation, both countries that apply civil law and common law legal systems. The tendency to form laws in Indonesia after the realization of the need for regulatory reform has resulted in a growing awareness of making breakthroughs by using the omnibus method which is generally applicable in countries that apply the common law system. The question is whether this method is suitable to be adopted into the legal system of Indonesia? This article intends to examine the compatibility of the omnibus method and the solutions that need to be used to overcome its compatibility problems. This research concludes that if Indonesia is to adopt the omnibus method, it also requires a consolidation method before and after the enactment of legislation with the omnibus method, this is intended to consolidate it with the affected legislation.